A Triple Threat? The Role of Diet, Nutrition, and the Microbiota in T1D Pathogenesis - Hamilton-Williams, Emma E.; Lorca, Graciela L.; Norris, Jill M.; Dunne, Jessica L. (Frontiers in Nutrition, 2021)
In recent years the role of the intestinal microbiota in health and disease has come to the forefront of medical research. Alterations in the intestinal microbiota and several of its features have been linked to numerous diseases, including type 1 diabetes (T1D). To date, studies in animal models of T1D, as well as studies in human subjects, have linked several intestinal microbiota alterations with T1D pathogenesis. Features that are most often linked with T1D pathogenesis include decreased microbial diversity, the relative abundance of specific strains of individual microbes, and altered metabolite production. Alterations in these features as well as others have provided insight into T1D pathogenesis and shed light on the potential mechanism by which the microbiota plays a role in T1D pathogenesis, yet the underlying factors leading to these alterations remains unknown. One potential mechanism for alteration of the microbiota is through diet and nutrition. Previous studies have shown associations of diet with islet autoimmunity, but a direct contributing factor has yet to be identified. Diet, through introduction of antigens and alteration of the composition and function of the microbiota, may elicit the immune system to produce autoreactive responses that result in the destruction of the beta cells. Here, we review the evidence associating diet induced changes in the intestinal microbiota and their contribution to T1D pathogenesis. We further provide a roadmap for determining the effect of diet and other modifiable factors on the entire microbiota ecosystem, including its impact on both immune and beta cell function, as it relates to T1D. A greater understanding of the complex interactions between the intestinal microbiota and several interacting systems in the body (immune, intestinal integrity and function, metabolism, beta cell function, etc.) may provide scientifically rational approaches to prevent development of T1D and other childhood immune and allergic diseases and biomarkers to evaluate the efficacy of interventions.